Legal Protection for Shareholders of Dissolved Insurance Companies - Oktaviandi Bangun Tri Anugrah Sitorus (CV. Publikasi Indonesia, 2024)
The capital market is the meeting place between supply and demand in trading securities, including stocks, which is proof of ownership of a company in exchange for shareholders' rights to profits or dividends. Although there are two main groups of shareholders, namely majority and minority, both groups have equal status in company ownership. To protect shareholders, capital market and limited liability company laws provide legal protection, including in cases of dissolution of insurance companies. In this research, normative legal methods were used to analyze relevant laws. The results show that shareholders' legal protection is contained in capital market and limited liability company laws, which give shareholders the right to file a lawsuit or request a company inspection if they feel aggrieved. The case of the dissolution of an insurance company by OJK shows that the institution can carry out its supervisory role and guarantee legal protection for shareholders by ensuring the company is responsible for losses incurred.